Arthrotomy, curettage and medical management of septic arthritis and osteomyelitis of the temporomandibular joint in a horse. (20th August 2019) - Balducci, J.; Ruby, J.; Hall, C.; Williams, J.
Summary: Osteomyelitis and/or bone sequestra are commonly reported in equids following traumatic wounds. This report describes the clinical management and outcome following an arthrotomy of the temporomandibular joint of a 1‐year‐old Quarter Horse gelding with septic osteomyelitis and arthritis. Computed tomography was used for further assessment of the lesions within the temporomandibular joint and helped guide surgical planning.